Centralized Platform for Managing Activities in E-Commerce Store - B.G.J.M Gamage; R.M.S.H Ranaweera; A.V.R.Dilshan; R. P. S. D Paranagama; D. I. De Silva; Samitha Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
This project is a web-based online shop management system for an existing store. This online shop management system mainly considers managing and automating the tasks in the online store. One of the main problems raised on existing systems was that there is no control with the admin user to manage items in the store. This system has users as Customers (Buyers), Admins, and Sellers. This proposed system allows these three users to manage their activities in a central platform. This research paper mainly discusses the main functionalities available in this system, how these functionalities are performed by each user, and the way that these functionalities are implemented and tested. An in-depth discussion of the tools and technology chosen to develop this system and the reason behind those choices are also included in this research paper.